Valproate activates ERK signaling pathway in primary human hepatocytes - Bitman, Michal; Vrzal, Radim; Dvořák, Zdeněk; Pávek, Petr (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2014)
AIM: Valproic acid (VPA) is a widely-used anticonvulsant and mood-stabilizing agent. VPA is also known to inhibit histone deacetylases (HDACs) affecting the expression of numerous genes. METHODS: In the present study, we examined the effect of VPA on the extracellular signal-related kinase (ERK, p42/p44) pathway (Ras-Raf-MEK-ERK) belonging to the mitogen-activated protein kinases (MAPKs) pathways in primary human hepatocytes. In the liver, the pathway is associated with progression of hepatocellular carcinoma. RESULTS: We found that VPA in a therapeutically relevant concentration (500 μM) activates the ERK pathway, as indicated by increased ERK Thr202/Tyr204 phosphorylation. Interestingly, a prototype HDAC inhibitor, trichostatin A, also activated ERK phosphorylation in primary human hepatocytes. These data suggest that HDAC inhibition might be the primary stimulus for ERK pathway activation in primary human hepatocytes. Notably, U0126, a MEK1 inhibitor, was ineffective in inhibiting ERK pathway activation, likely due to its metabolic deactivation in metabolically competent primary human hepatocytes. CONCLUSION: We conclude that VPA activates the ERK pathway in primary human hepatocytes.
Keywords: hepatocyty; kyselina valproová; Hepatocytes; MAP Kinase Signaling System; Histone Deacetylase Inhibitors; kyseliny hydroxamové; lidé; Cells, Cultured; inhibitory histondeacetylas; fosforylace; Valproic Acid; MAP kinasový signální systém; Phosphorylation; Hydroxamic Acids; kultivované buňky; Humans